Protective Role of Vaccination against Tuberculosis and Hepatitis B in Prevention of Atopic Dermatitis: Report on Intermediate Results of Prospective Cohort Study - Veronika A. Petrova; Leyla S. Namazova-Baranova; Marina V. Fedoseenko; Dina S. Rusinova (Педиатрическая фармакология, 2023)
Background. Studies have shown that vaccination in the first hours/days after birth shifts the immune response from intrauterine Th2 towards Th1-type activation and reduces the risk of atopic conditions. However, we did not find published data from prospective studies on this topic.Objective. The aim of the study is to define the presence of negative correlation between vaccination against tuberculosis and hepatitis B in the first hours/days of life and atopic dermatitis development in infants.Methods. Continuous prospective study of children cohort born from April to June 2021 and observed in one outpatient’s clinic was carried out. Data from 307 infant’s records (F. 112/y), vaccination record cards (F. 063/y), prenatal and delivery records (F. 113/y-20, section № 3), and neonatal discharge summaries were analyzed for the decreed period. The child vaccination status (by the time of vaccination against tuberculosis and hepatitis B), presence of risk factors for allergic disease development, and presence of atopic dermatitis were evaluated.Results. Atopic dermatitis (AD) was significantly less likely to be diagnosed by the age of 1 year in infants from the group of BCG-M vaccinated at maternity hospital than in those vaccinated later or not vaccinated at all (15.2% versus 66% and 35.7%, respectively; p < 0,01). AD was less likely to develop in children with risk factors for allergic disease who were vaccinated against tuberculosis in the maternity hospital than in those vaccinated later or unvaccinated at all (18, 75 and 62.5%, respectively; p < 0.01). The ratio of children with diagnosed AD by the age of 12 months was significantly less in the group of children vaccinated against hepatitis B in the maternity hospital than in those vaccinated later or unvaccinated at all (17.6, 44.9 and 31.8%, respectively; p < 0.01). These ratios for children with risk of allergic disease development were 24%, 50% and 44.4%, respectively (p = 0.043). It has also been shown that timely vaccination with both vaccines in the early neonatal period significantly reduces the risk of AD in general infant population compared to non-vaccinated individuals or those who had only one vaccine (odds ratio [OR] 0.374; 95% confidence interval [CI] 0.253-0.552; p < 0.01). Whereas the disease development in children with allergic risk is less likely with timely vaccination (20.8% versus 53.3%; OR = 0.252; 95% CI 0.145–0.440; OR = 0.374; 95% CI 0,253–0,552; p < 0,01).Conclusion. The obtained results may indicate possible risk reduction for AD development due to timely preventive vaccination against tuberculosis and hepatitis B, especially in children with allergic risk. The study is currently ongoing.